Opportunistic Pathogens of Recreational Waters with Emphasis on Antimicrobial Resistance—A Possible Subject of Human Health Concern - Stec, Joanna; Kosikowska, Urszula; Mendrycka, Mariola; Stępień-Pyśniak, Dagmara; Niedźwiedzka-Rystwej, Paulina; Bębnowska, Dominika; Hrynkiewicz, Rafał; Ziętara-Wysocka, Joanna; Grywalska, Ewelina (International journal of environmental research and public health, 2022)
Infections caused by exposure to opportunistic pathogens can cause serious health problems during recreational water use. The problem of diseases caused by microbes transmitted by water is a major public health challenge, especially in developing countries with economic problems and poor hygiene conditions. Moreover, the quality of water in natural reservoirs is often at a very low level in terms of microbiological water purity, which means that their use for recreational purposes, but also as a source of drinking water, may have serious health consequences. Recreational waters pose a threat to human health. Therefore, the quality of recreational waters is closely monitored in many jurisdictions. In this review, we summarize key information on the most common pathogens that can be water-based or waterborne. The issue of antimicrobial resistance among opportunistic pathogens remains equally important. It is important not only to fight pathogens, but also to take action to reduce chemical stressors (especially antibiotics) in the aquatic environment, and to understand the various mechanisms of the spread of antibiotic-resistant genes.